Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan - Huang, Jian-Fu; Ho, Hsuan-Ching; Chang, Yung-Hsu; Smith, David G.; Chen, Hong-Ming (Zootaxa, 2018)
Two new species of the congrid eel genus Bathycongrus are described from the deep waters of eastern Taiwan. Bathycongrus albimarginatus sp. nov., which belongs to the species group with two enlarged teeth on the vomer and more total vertebrae, is described from 16 specimens and can be distinguished by vertical fins with broad white margins, more pores on head and predorsal lateral line, total vertebrae 195–201. Bathycongrus brunneus sp. nov., which has no enlarged teeth on the vomer, is described from one specimen and can be distinguished by 12 subequal teeth on the vomer and 174+ total vertebrae.